Słownikowe homografy czasownikowe w języku rosyjskim - Kaliszan, Jerzy (Studia Rossica Posnaniensia, 2017)
The author analyzes the homographic potency of Russian verbs stressed differently in their infinitive forms, such as úкать — икáть, трýсить — трусúть, срéзать — срезáть etc. In contemporary Russian there are about 350 of these pairs. They are able to create over 3,200 pairs of predicative homographs and almost 27,000 pairs of attributive (participial) homographs.